RECONFIRMATION OF RARE PLANTS ON THE NORTHWESTERN BLACK SEA COAST - Mihai DOROFTEI; Simona Dumitriţa CHIRILĂ; Silviu COVALIOV; Adrian OPREA; Culiţă SÎRBU (Journal of Plant Development)
Rare plant species are particularly vulnerable to anthropogenic influences, which contribute to reducing their populations and restricting their distribution areas. The objective of this study was to reconfirm the information on the distribution of three rare plant species – Tripidium ravennae, Trachomitum venetum, and Stachys maritima, within the Danube Delta Biosphere Reserve, Romania. The research was carried out between 2019 and 2023. The results highlighted that the respective species are rare by showing limited distribution and small populations. Among the main threats to the survival of these species are tourism development, overgrazing, and soil compaction. Trachomitum venetum is a rare plant species in specific communities, showcasing its selective habitat preferences. Tripidium ravennae is a rare species in specific plant subassociations and plant associations, indicating its limited distribution. Stachys maritima is rare within different plant communities, reflecting its adaptability to varied environmental conditions within the Danube Delta Biosphere Reserve.